Dynamic 18F-FDG-PET kinetic parameters for epileptogenic zone localization in drug-resistant epilepsy - Khamwan, Kitiwat; Sukprakun, Chanan; Limotai, Chusak; Jirasakuldej, Suda; Jantarato, Attapon; Hemachudha, Thiravat; Tepmongkol, Supatporn (Frontiers in Physics, 2023)
Objective: Precisely localizing the seizure onset zone remains a challenging task in drug-resistant epilepsy (DRE) patients especially given its critical role in successful surgery and effective management. This study aimed to investigate the kinetic parameters of regional 18 Ffluorodeoxyglucose (FDG) uptake in DRE patients, aiming to identify the kinetic parameters best enabling the identification of the epileptogenic region. Methods: Consecutive DRE patients with clinically mandated interictal 18 F-FDG PET/CT were recruited from October 2019 to September 2020 for pre-surgical evaluation. Immediately after injecting 18 F-FDG of 112-179 MBq, dynamic data were acquired for 90 minutes. The motion correction and resampling to the Montreal atlas was performed in order to generate a transformation matrix. 116 volume of interests (VOIs) and regional time-activity curves (TACs) were generated by employing the automated anatomical labeling (AAL) template using PMOD software. Kinetic parameters of FDG unidirectional blood-brain clearance (K1), efflux (k2), phosphorylation (k3), and This is a provisional file, not the final typeset article net metabolic flux (Ki) were derived using irreversible 2-tissue-compartment model with an imagederived input function (IDIF). The kinetic parameters values obtained from all regions were ranked and compared with the presumed epileptogenic zone (EZ). Results: Eleven DRE patients (5 males, 6 females, mean age 35.1±10.2 years) were analyzed. We found that the region with the lowest values of Ki provided correct lateralization in 7/7 (100%) of patient with temporal lobe epilepsy (TLE) and the region with the lowest Ki and k3 parameters showed concordance with the EZ in 100% and 71.4% of patients, respectively.The present parametric approach to the evaluation of FDG-PET may be more sensitive than semi-quantitative approaches for the detection of pathophysiology in the EZ of patients with medically unresponsive TLE in addition to the routine clinical investigations.